Investigation on nitrogen removal performance of an enhanced post-anoxic membrane bioreactor using disintegrated sludge as a carbon source: An experimental study. Issue 6 (December 2019) - Fathali, Davoud; Rashidi Mehrabadi, Abdollah; Mirabi, Maryam; Alimohammadi, Mahmood
Abstract: In this study, a Post-Anoxic Membrane Bioreactor (PA-MBR) has been proposed to enhance nitrogen removal from real domestic wastewater. The system comprised an aeration tank followed by an anoxic chamber in which a membrane module was immersed. For effective proliferation of denitrifiers, acetate in the form of vinegar and later the disintegrated sludge through ultra-sonication were used as the carbon source for denitrification. The main goals of this study were enhancing the biological nitrogen and COD removal and investigating the influential aspects of using disintegrated sludge as a readily biodegradable COD in the PA-MBR system. The fouling behavior of the membrane was also studied as a consequent drawback of membrane application in the anoxic environment, through monitoring the trends of Transmembrane Pressure (TMP) increase over time along with the Scanning Electron Microscopy (SEM) studies. The results showed that the system in its steady-state conditions was able to remove 93.24% and 94.57% of COD and TN contents, respectively. The observed COD, TN, NO3 − -N, TSS and turbidity contents of the effluent were equal to 28 ± 4.85 mg/L, 1.69 ± 0.33 mg/L-N, 1.52 ± 0.29 mg/L-N, <1 mg/L and <0.18 NTU, respectively. Furthermore, the membrane demonstrated a consistently superb performance, despite its application in the anoxic environment. Using physical cleaning of the membrane surface by a water jet every two to five days instead of conventional chemically enhanced backflush, the membrane's chemical cleaning intervals were extended up to five weeks.